Generalized Gingival Enlargement in Young Adult with Chronic Periodontitis: A Case Report - Aurelia Krisnadita; Vania Christina Budiono Bang; Johanna Kezia Prajogo; Kurnia Nisa Putri Firawan; Isniya Nosartika (RSUP Dr. Kariadi, 2025)
BACKGROUND: Dental plaque is a natural biofilm that, if inadequately controlled, can lead to gingivitis and chronic inflammatory gingival enlargement. Persistent gingival overgrowth may impair both function and aesthetics, often requiring surgical intervention such as gingivectomy, when non-surgical treatments prove ineffective. CASE REPORT: A 22-year-old male presented with swollen and bleeding gums. Patient reported no history of systemic diseases or the use of any specific medications. Intraoral examination revealed gingival hyperemia, enlargement, and carious lesions on multiple teeth. Despite initial treatment with scaling root planing (SRP) and oral hygiene instruction, gingival enlargement persisted. Panoramic radiography revealed additional findings, including alveolar crest resorption and impacted third molars. A four-stage gingivectomy was performed under local anesthesia, followed by postoperative care, including antibiotics (Clindamycin), analgesics, mouthwash, and strict oral hygiene maintenance. Restorative treatments and splinting of mobile teeth were also carried out. DISCUSSION: The patient's gingival enlargement was primarily plaque-induced, further exacerbated by local factors such as dental caries. Scaling and root planing (SRP) alone proved insufficient due to the presence of fibrotic tissue, necessitating surgical intervention via gingivectomy. Postoperative healing was successful, with notable improvements in gingival contour, consistency, and oral hygiene indices. Patient education and adherence to postoperative care were crucial in achieving favorable outcomes. CONCLUSION: Effective management of chronic inflammatory gingival enlargement requires accurate diagnosis, appropriate initial therapy, and surgical intervention when indicated. In this case, staged gingivectomy, combined with comprehensive oral care, successfully restored gingival health and aesthetics, emphasizing the importance of individualized treatment planning and patient cooperation.